PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 19 PADANG - Agustina, Indah; Abdurrahman, Abdurrahman (Universitas Negeri Padang, 2019)
ABSTRACTThe purpose of this study is (1) to determine the level of skill of writing disscusion text of grade VIII of SMP Negeri 19 Muara Padang before using problem based learning model. (2) to determine the level of writing’s skill on fable text of grade VII of SMP Negeri 19 Padang after using problem based learning model. (3) analyze the effect application problem based learning model assisted to the skill of writing fable text in grade VII students of SMP Negeri 19 Padang. This type of research is quantitative experimental method. Based on data analysis, using problem based learning model toward students writing’s skill on fable text in grade VII students of SMP Negeri 19 Padang.Kata Kunci: Pengaruh Model Problem Based Solving, Keterampilan Menulis Teks Tabel